2003
DOI: 10.1194/jlr.m300092-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unsaturated fatty acids and triacylglycerols on phosphatidylethanolamine membrane structure

Abstract: Lipid intake in diet regulates the membrane lipid composition, which in turn controls activities of membrane proteins. There is evidence that fatty acids (FAs) and triacylglycerols (TGs) can alter the phospholipid (PL) mesomorphism. However, the molecular mechanisms involved are not fully understood. This study focuses on the effect of the unsaturation degree of the C-18 FAs, oleic acid (OA), linoleic acid and linolenic acid, and their TGs, triolein (TO), trilinolein, and trilinolenin, on the structural proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…The lamellar phase is observed up to 75°C with a continuous minor decrease in the lattice parameter, indicating dehydration accompanied by increasing alkyl chain fluidity, as observed in many phospholipids, e.g., ref 18. More interesting is the lattice variation of the cubic phases, which expand until the It is worth noting two aspects: (a) both cubic phases followed similar thermal evolution of their lattice sizes up to 75°C, when the P4 3 32 vanishes.…”
Section: ' Results and Discussionmentioning
confidence: 92%
“…The lamellar phase is observed up to 75°C with a continuous minor decrease in the lattice parameter, indicating dehydration accompanied by increasing alkyl chain fluidity, as observed in many phospholipids, e.g., ref 18. More interesting is the lattice variation of the cubic phases, which expand until the It is worth noting two aspects: (a) both cubic phases followed similar thermal evolution of their lattice sizes up to 75°C, when the P4 3 32 vanishes.…”
Section: ' Results and Discussionmentioning
confidence: 92%
“…The outcome of these measurements was compared with results obtained for a series of structurally and chemically related fatty acids and TO ( Fig. 6) (3,4). We found that there was a tendency for the reduction induced by these lipids on BP to be correlated with the in vitro effect on the L-to-H II phase transition (r ϭ 0.67; P ϭ 0.07; n ϭ 8) (Fig.…”
Section: Effects Of Voo On Bp In Spontaneously Hypertensive Rats (Shrs)mentioning
confidence: 99%
“…We assessed the effect of VOO and soybean oil on membrane lipid structure, and we found that, in agreement with the effect exerted by their major TGs constituents, both oils induced marked reductions in the L-to-H II phase transition (3). The outcome of these measurements was compared with results obtained for a series of structurally and chemically related fatty acids and TO ( Fig.…”
Section: Effects Of Voo On Bp In Spontaneously Hypertensive Rats (Shrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This drug interacts with cell membranes, inducing changes in their composition and structure (1,11,12), and it triggers a series of events that ultimately result in the dramatic knockdown of the proliferation-inducing transcription factor E2F-1 (3).…”
mentioning
confidence: 99%